Continuity in ovine Johne's disease vaccination practices despite a decline in clinical disease. Issue 9 (2nd June 2021) - Green, AC; Plain, KM; Eppleston, J; Martinez, E; Emery, D; Dhand, NK
Abstract : The Gudair® vaccine has been commercially available in Australia for almost two decades for the control of ovine Johne's disease, but concerns have been raised about potential discontinuation of vaccination by producers after a decline in the incidence of clinical disease. An online questionnaire was distributed to Australian sheep producers to identify the proportion of respondents discontinuing the Gudair vaccine and reasons for discontinuation. Results revealed that 88% of sheep producers surveyed have continued to vaccinate their sheep with Gudair, with continuation greater for predominantly Merino sheep flocks. Reasons for discontinuing vaccination stemmed from management, economic or health concerns. These results suggest that Gudair is still widely used by Australian sheep producers and concerns about large‐scale discontinuation are unfounded. These findings have implications for ovine Johne's disease control programs in Australia.